Does telephone intervention affect adherence to antiretroviral therapy in women with human immunodeficiency virus - Samyla Citó Pedrosa; Ivana Cristina Vieira de Lima; Bárbara de Abreu Vasconcelos; Gilmara Holanda da Cunha; Maria Lúcia Duarte Pereira; Marli Teresinha Gimeniz Galvão (Rev Rene)
Objective: to evaluate the impact of a telephone intervention on the adherence to antiretroviral therapy in women with human immunodeficiency virus. Methods: quasi experimental study, before and after, conducted ina specialized service with 19 women who live with the human immunodeficiency virus. The study was developedin four phases: recruitment; assessment of adherence to antiretroviral treatment, telephone intervention and reassessment of adherence. During three months of follow-up, eight calls were made to each participant, totaling 152 interventions. Results: there was a statistically significant improvement in the number of participants with adequate adherence (p=0.004) and in the mean of adherence scores (p=0.000) after the intervention. There was no significant impact on the immune status. Conclusion: telephone interventions aimed at women with human immunodeficiency virus developed during three months proved to be effective for improving adherenceto treatment.